Entre palavras, formas e cores : as redondilhas de Camões e as pinturas de Bruegel - Vicentini, Inez Paggi (2011)
The discussions between verbal and non-verbal texts of this dissertation aim to contribute to the critical richness of the studies of Camões and the painting of Pieter Bruegel, highlighting the visual-verbal power of the poetic writings in ancient measure and the images of the painting, comparatively focusing the woman in her daily job on a rural environment, her profile and her mood. Luis Vaz de Camões (1524?-1580), the greatest Portuguese poet of all time, brings back the medieval tradition to compose a big part of his lyric poetry in ancient measure, following the steps of the Galician-Portuguese lyric and the palace's poetry, gathered in Cancioneiro Geral, by Garcia de Resende (1470?-1539), and also the rhetorical resources used in this kind of poetry. Pieter Bruegel (1525-1569) lived and produced his paintings in the big towns of the region known as Flandres, situated on actual Belgium, and he is considered one of the greatest painters and drawers of the Sixteenth Century. Over the Renaissance, his work departs from the idea of perfection of the period by portraying the life in the little villages that still preserved the medieval habits, in a proper style of painting. This study justifies itself by the need of valorizing the image like an element of constant presence in the verbal and pictorial arts. The research is based on the theoretical principles of the Comparative Aesthetical and Comparative Literature, following the ideas of Souriau, Praz, Joly, Aguiar e Silva and others. The concepts of the Aesthetic of Reception, by Iser and Eco, were also considered. Historians like Gombrich, Auerbach, Strickland, among others, were utilized as basis of the study of the selected paintings and texts. It is on the image produced by the word and in the word inspired by the image that mankind can perceive itself and feel itself in its reality.